Hydro chemical facies and physico-chemical characterization of thermal spring water of Unkeshwar, Maharashtra - Mangle, Vijay S (International Multidisciplinary Research Journal, 2012)
The physical and chemical parameters of groundwater play a significant role in classifying and assessing water quality. Major ions constitute the most significant part of the total dissolved solids present in the groundwater and the concentration of these ions in ground water depends mainly on the hydro chemical processes that place in the aquifer system. The diagnostic chemical character of water solutions in hydrologic systems has been determined with the application of the concept of hydro chemical facies. The temperature of the thermal spring water not was 43and 45 0 C, the pH value for water is 7.2 and 7.5. The observed trend of dissolved oxygen is controlled by temperature of water, i.e. 5.8 mg/L in November and 5.2 mg/L in March. The hardness of water was 138 mg/L to 138 mg/L. The magnesium decreased from 5.3 mf/L to 3.41 mg/L, the chlorides increased from136 mg/L to 284.3 mg/L in November to march whereas sulphates decreased from 72.81 mg/L to 13.7 mg/L. The Ca-Mg-Na plot conforms thermal water falls in Ca-Mg domain.